A jornada das heroínas no cinema de animação: mitos, fantasia e símbolos em Alice no País das Maravilhas e a Viagem de Chihiro - Cavalcante, Alexia Eloar Félix (2021)
Alice in Wonderland (1951) has attracted a large audience, from children to adults, for over a century, with many remakes and adaptations produced in different media. But it was in the USA, in the 50s, that Walt Disney was able to adapt in his studio the work of the Englishman Lewis Carroll into animated feature film. In Japan, famous for its anime and manga, there is Studio Ghibli, one of the major names in oriental animation. Among the many works that were produced, with the majority of it having a female protagonist, Hayao Miyazaki, one of the studio’s founders, gave us Chihiro, in Spirited Away (2001). In this research, we look through the eyes of Alice and Chihiro, using the theory of focalisation (GENETTE, 2017; STAM, 1992), that we follow their departure from similar structures in a moment of self-discovery with the transition between childhood and adult life to the heroine’s journey. Along with these objects we intend to understand the art of animation, with support from Fossati (2011) and Graça (2006), as a delegation of voices, paying attention to what stories are being told, by whom they are being told and how they were produced, disseminated and received by the public (SHOHAT, STAM, 2006). This work seeks to show which stereotype elements remain and which are broken up based on the analysis of the archetype of the hero’s journey, by Joseph Campbell (1989), compared to the heroine’s journey, by Maureen Murdock (2013). These models will be used to realize how the emotional gaze of Alice and Chihiro has significant value in their filmic animations, bringing specific issues of the female gender in their journeys of self-knowledge based on myths and symbols, based on the studies of Bachelard (1978, 1996, 1998), J. Brandão (1987), Chevalier and Gheerbrant (1986, 1982, 2015), Eliade (1979, 1996), Kato (2012) and Mendlesohn (2008), both in the West and in the East.